Active Salt/Silica‐Templated 2D Mesoporous FeCo‐Nx‐Carbon as Bifunctional Oxygen Electrodes for Zinc–Air Batteries - Li, Shuang; Cheng, Chong; Zhao, Xiaojia; Schmidt, Johannes; Thomas, Arne (Angewandte Chemie International Edition, 2018)
Two types of templates, an active metal salt and silica nanoparticles, are used concurrently to achieve the facile synthesis of hierarchical meso/microporous FeCo‐Nx‐carbon nanosheets (meso/micro‐FeCo‐Nx‐CN) with highly dispersed metal sites. The resulting meso/micro‐FeCo‐Nx‐CN shows high and reversible oxygen electrocatalytic performances for both ORR and OER, thus having potential for applications in rechargeable Zn–air battery. Our approach creates a new pathway to fabricate 2D meso/microporous structured carbon architectures for bifunctional oxygen electrodes in rechargeable Zn–air battery as well as opens avenues to the scale‐up production of rationally designed heteroatom‐doped catalytic materials for a broad range of applications. Meso/microporous Fe/Co‐Nx‐doped carbon nanosheets prepared by an active salt/silica nanoparticle templating approach achieve high performance as bifunctional oxygen electrodes. The FeCo‐Nx‐carbon has a well‐defined 2D morphology and homogenous metal‐atom doping, yielding enriched active sites for ORR‐OER. These features lead to excellent reversible oxygen electrocatalytic performance for Zn–air batteries.